Detecting triplet states in opto-electronic and photovoltaic materials and devices by transient optically detected magnetic resonance. Issue 9 (10th August 2021) - Grüne, Jeannine; Dyakonov, Vladimir; Sperlich, Andreas
Abstract : We present a transient ODMR technique to detect and distinguish triplet states in opto-electronic and photovoltaic materials and devices. Abstract : Triplet excited states in organic semiconductor materials and devices are notoriously difficult to detect and study with established spectroscopic methods. Yet, they are a crucial intermediate step in next-generation organic light emitting diodes (OLED) that employ thermally activated delayed fluorescence (TADF) to upconvert non-emissive triplets to emissive singlet states. In organic photovoltaic (OPV) devices, however, triplets are an efficiency-limiting exciton loss channel and are also involved in device degradation. Here, we introduce an innovative spin-sensitive method to study triplet states in both, optically excited organic semiconductor films, as well as in electrically driven devices. The method of transient optically detected magnetic resonance (trODMR) can be applied to all light-emitting materials whose luminescence depends on paramagnetic spin states. It is thus an ideal spectroscopic tool to distinguish different states involved and determine their corresponding time scales. We unravel the role of intermediate excited spin states in opto-electronic and photovoltaic materials and devices and reveal fundamental differences in electrically and optically induced triplet states.